Penyelesaian Konflik Pertanahan di Provinsi Lampung - Dimiyati Gedung Intan (Universitas Bandar Lampung (UBL), 2011)
This study is about land conflict resolution In Lampung Province. The legal frameworkis land in forest areas in the register 45 and the other forest regions. Later this studywill discuss also foundation for local governments and communities to resolve landconflicts in each district in Lampung province which as a basis for achieved longtermdevelopment objectives, namely address the problems of poverty, developcommunity economic system, development of economic stability and environmentalpreservation. Rights granting Industrial Forest Plantation Management should beexamined in order to prevent illegal activities in forests Register 45, because itsmanagement is not in accordance with permission granted to the company. Localgovernment should helps to resolve land dispute with communities affected bycompany, which has not been held and compensation have not been register, right tocultivate the National Land Agency, and examine the documents that exist in thecompany.